Unveiling gendered perspectives on farmers’ climate risk perception, and adaptation strategies: A systematic review - Ningombam, Soniya; Das, Abhishek; Kumar, Shalander; Kasala, Kavitha; Puskur, Ranjitha (International Crops Research Institute for the Semi-Arid Tropics, 2023)
Climate change poses a significant challenge to farmers worldwide. It affects men and women differently due to their diverse roles, responsibilities, resource access and sociocultural norms. Understanding the gender perspective would help policymakers to develop evidence-based strategies that address unique vulnerabilities, promoting equitable, inclusive adaptation and resilience policies to climate risk. Hence there is a need to evaluate the available evidence base on gendered perspectives in this domain to design effective adaptation policies as well as future research. This systematic review—utilizing Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) technique using three databases (Web of Science, PubMed and CABI review) and analyzing 152 studies from 32 countries—unveils nuanced gender perspectives and evidence gaps on the subject. The insights from the study show variations among men and women farmers in their perceptions of climate risk attributes in agriculture. For instance, men’s perception of temperature predominantly revolves around its immediate consequences on crop growth and farm management, while women farmers consider broader implications on household food security and community resilience. These varied gendered perceptions arise from divergent roles, responsibilities, and social and economic status. Adaptation strategies also differed, for example, with men adopting advanced approaches while women often rely on traditional knowledge as their primary means of adaptation. This study not only identifies the literature gap on climate change impacts and adaptation with a gender lens, but also highlights the need for recognizing and incorporating gender-responsive climate adaptation strategies into policy and practice for promoting climate resilience, sustainable livelihoods and agri-food systems.